Urban Memory Becomes An Idea In The Concept of Spatial Planning (Study Case: Restoration Area of Tambora District, West Jakarta) - Phillia, Riska; Sihombing, Antony (Smart City, 2023)
Urban heritage is a small part of the past of the city that holds the roots of the city's identity and culture, which are the city's identity. The strong identity of the historic area must be maintained, but this has a dilemma because of the need for change today. Therefore efforts are needed to create adaptive urban heritage areas. City spaces have a deep relationship with the people who inhabit them, with the most memorable or most memorable experiences and memories for them. This research contributes to exploring urban memory to develop conceptual spatial plans in restoration areas, using qualitative research methods to study and seek in-depth information about human behavior or phenomena in the area. The mapping method is a semi-structured map-based interview to evaluate structural (physical) integrity and conduct semi-structured interviews to assess dynamic (non-physical) integrity. This study found that people who live or work in this restoration area have a strong memory or memory of the urban heritage in their area. However, it is different for those who visit; visitors must fully understand and remember the area's history. This study suggests that if physical manipulation is carried out in the area, it starts by strengthening the site's structural integrity because environmental quality is vital for the security and visualization of the area. Then, it requires dynamic integrity for values that connect people to a more dynamic approach to urban heritage conservation. The community's collective memory includes the city's heritage values and, if properly preserved, can increase the heritage value over time and add to the area's economic value.